Genetic parameters and multivariate analysis for morphological and some boll anatomical traits of intra and interspecific crosses of cotton - Harb, R.K.; El-Feki, T.A.; Sultan, Aziza, M. (2006)
The present study was carried out at Giza Resean; h Station during 2002, 2003 and 2004. A partial diallel cross system among eight parents were used to estimate, hybrid vigor, inbreeding lkpression, potence ratio, general and specific combining ability for morphological traits as well as, anatomical traits of bolls. Multivariate analysis was used to determine the intcrcorrelation between these traits and infestation percent of bollworms and to clear importance of these lraits.
Includes reference.
Summary in Arabic.
1
Keywords: Cotton -- Genetics; Cotton -- Breeding; Cotton -- Diseases and pests